2022
DOI: 10.32604/cmc.2022.022322
|View full text |Cite
|
Sign up to set email alerts
|

Automated Deep Learning Empowered Breast Cancer Diagnosis Using Biomedical Mammogram Images

Abstract: Biomedical image processing is a hot research topic which helps to majorly assist the disease diagnostic process. At the same time, breast cancer becomes the deadliest disease among women and can be detected by the use of different imaging techniques. Digital mammograms can be used for the earlier identification and diagnostic of breast cancer to minimize the death rate. But the proper identification of breast cancer has mainly relied on the mammography findings and results to increased false positives. For re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
(21 reference statements)
0
9
0
Order By: Relevance
“…Autoencoders combine an encoder and a decoder to reconstruct the input information using a compressed representation. (Escorcia-Gutierrez et al, 2022) It combines wavelet analysis and neural networks. It uses wavelets to extract time-frequency features from input data and then combines these features into a neural network to learn complex patterns.…”
Section: Techniques References Descriptionmentioning
confidence: 99%
“…Autoencoders combine an encoder and a decoder to reconstruct the input information using a compressed representation. (Escorcia-Gutierrez et al, 2022) It combines wavelet analysis and neural networks. It uses wavelets to extract time-frequency features from input data and then combines these features into a neural network to learn complex patterns.…”
Section: Techniques References Descriptionmentioning
confidence: 99%
“…The findings demonstrated that the suggested model achieves accuracy, specificity, and sensitivity rates of 91.5%, 72.4%, and 94.1%, respectively. In 39 , an automated DL-based BC diagnosis (ADL-BCD) algorithm was introduced utilizing mammograms. The feature extraction step used the pretrained ResNet34, and its parameters were optimized using the chimp optimization algorithm (COA).…”
Section: Related Workmentioning
confidence: 99%
“…According to empirical analysis, when it comes to the training-test ratio, the best results are obtained when 70–90% of the initial data are used for training and the rest are used for testing 43 , 44 . In addition, 70%, 80%, and 90% dataset splitting ratios are most frequently used for training, as seen in 12 , 13 , 18 , 23 , 31 , 39 , and 16 , 30 , 39 , 41 , respectively.…”
Section: Related Workmentioning
confidence: 99%
“…Table 1 shows the Results of comparing the study with some of the other studies that aimed to improve breast cancer diagnostic images using several techniques. They were compared in terms of samples, methods, results, and the contribution of each study [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ].…”
Section: Literature Reviewmentioning
confidence: 99%